Modified Pereira Suture as an Effective Option to Treat Postpartum Hemorrhage due to Uterine Atony - Moleiro, M. (2020)
Nowadays, postpartum hemorrhage is the major cause of maternal mortality and morbidity worldwide. Uterine atony is its main cause; thus, prophylactic measures, as well as medical and surgical fast approaches, have been developed to manage it. The uterine compression sutures are a possible treatment that preserves the uterus and, consequently, the fertility potential. Bearing that in mind, we report two cases of postpartum hemorrhage after caesarean section, successfully treated with a new modification of Pereira suture - longitudinal and transverse uterine sutures were applied after no response was registered to the first-line therapies. Both women recovered, and the postpartum evaluation revealed a normal uterus with an adequate blood supply, suggesting potential fertility, as described in the literature regarding this kind of therapeutic approach.